Mathematics
Marmar11
42

Systems of equations I need help and show your work to

+4
(1) Answers
TiandaC

I started by using elimination to solve for x 3x + 9 = -3y              became            -2x - 2 = 0      -5x - 11 = 3y    then i soved for x -2x = 2        x = 2/-2      x = -1 then i plug that back in for x and sove for y in one of the original equations first equation 3(-1) + 9 = -3y     6 = -3y     6/-3 = y     y = -2 second equation 3y = -5(-1) - 11    3y = -6    y = -6/3      y = -2 therefore your answers are x = -1 and y = -2

Add answer